Pembelajaran (Learning) sebagai Upaya Pemberdayaan SDM - Helio Augusto Da Costa Xavier M. (Universitas Islam Indonesia, 2004)
Basically, the role of human being in companies in tight competition situation like this time is to take the decision and yield the innovation which cannot be replaced by technology as sophisticated as any. Therefore human resource empowerment through learning is important be achieved because empowerment itself represent a way to: - entrepreneurship people; - sense of belonging Cultivation (Ownership); - shape the commitment (engagement); - Entangle the activity insider (Involvement). Human resource empowerment represent difficult concept to understand fully and hard in applying. However if human resource empowerment disregarded of course waste in the appliance which can make a company reach the efficacy in the future. Through learning, employee was expected to show a behavioral change in work, this behavioral always refer to what have been known or comprehended by employees in learning (knowledge), what they do (skills), what can they think (attitudes) and they were reflected on what they do (action). Keywords: Human Resource, Learning, Empowerment, Behavior.